The influence of neurovegetative and psychological characteristics of infertile patients with long-term COVID-19 on the effectiveness of assisted reproductive technologies - O.G. Boichuk; I.S. Golovchak; T.V. Kolomiichenko (Український журнал Здоров'я жінки)
The connection of the long-COVID-19 symptom with violations of various systemic factors, in particular with the female reproductive system, is considered, but the number of such studies is not large.